2018
DOI: 10.1159/000486140
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Changes and Caries-Preventive Effect of an Innovative Varnish Containing Chlorhexidine in Orthodontic Patients

Abstract: The aim of this study was to investigate the effects of Cervitec Plus® on the level of mutans streptococcus (SM) and lactobacillus (LB) colonies and the development of white spot lesions (WSLs) in patients with fixed orthodontic appliances. Informed consent was obtained from 32 volunteers (age 16.5 ± 2.75 years). At baseline, levels of the bacterial colonies were determined in saliva and plaque using a chairside test (CRT Bacteria, Ivoclar-Vivadent, Schaan, Liechtenstein), and the number of WSLs was registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…The aim of the present study was to determine whether it was possible to produce elastomeric ligatures capable of sustained chlorhexidine release. The utility of topical CHX products in reducing microbial colonisation and inhibiting the formation of WSL in orthodontic patients is widely recognised 21,22,23 . CHX digluconate and diacetate have both previously been incorporated into prototype ligatures comprised of three polyurethane layers.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to determine whether it was possible to produce elastomeric ligatures capable of sustained chlorhexidine release. The utility of topical CHX products in reducing microbial colonisation and inhibiting the formation of WSL in orthodontic patients is widely recognised 21,22,23 . CHX digluconate and diacetate have both previously been incorporated into prototype ligatures comprised of three polyurethane layers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite hygiene therapies for the control of dental caries/WSLs, the frequency of WSLs in orthodontic treatments remains significantly high. Several studies have demonstrated that from 2% up to 96% of the patients with this kind of therapies could strongly develop conditions to increase the risk of WSLs in subjects with orthodontic appliances [3,[11][12][13]; indicating, in some cases, that more than 50% of subjects with fixed orthodontic appliances might experience an increased risk in the number of WSLs during the orthodontic treatment [14]. This is a clinical problem that might create an unacceptable esthetic alteration that, in some severe cases, may involve restorative treatments [11].…”
Section: Introductionmentioning
confidence: 99%
“…This is a clinical problem that might create an unacceptable esthetic alteration that, in some severe cases, may involve restorative treatments [11]. Dental protocols for the prevention and control of WSLs based on fluoride tools have been the most successful treatments [12,13]; moreover, other alternative protocols using innovating varnishes have recently demonstrated to have different physicochemical properties to the control of the development of incipient dental caries [14,15]. Recently, silver nanoparticles (AgNPs) have been shown to be materials with excellent antimicrobial properties in a wide variety of microorganisms [6,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The patients' characteristics, including the Modi ed Gingival Indices (MGI) characteristic for the gingival condition [35,36], are summarized in Supplementary table 1. Fixed orthodontic appliances were placed on the labial tooth surfaces (more than 1.5 mm from the gingival margin) according to the professional rules with an acid-etch composite system (Transbond XT, 3M Unitek, Neuss, Germany), as in an earlier study [37].…”
Section: Study Design and Recruitment Of Participantsmentioning
confidence: 99%